A randomized cross over trial of tolerability and compliance of a micronutrient supplement with low iron separated from calcium vs high iron combined with calcium in pregnant women [ISRCTN56071145] - Couturier Bernard; Cérat Yves; Pairaudeau Nicholas; Pairaudeau Nicholas; Ahn Eric; Fortier Andre; Paradis Éric; Koren Gideon (BMC, 2006)
Abstract Background Prenatal micronutrient combinations with high iron content are associated with high rates of gastrointestinal symptoms. This coupled with nausea and vomiting of pregnancy results in women often discontinuing their multivitamins. A new prescription supplement (PregVit®) that separates iron from calcium in two tablets - morning and evening, has lower elemental iron content (35 mg), but results in similar extent of iron absorption when compared to another supplement containing (60 mg) of elemental iron (Materna®). The objectives of this study were to compare tolerability and compliance with PregVit® vs. a supplement with high iron content (Materna®), in pregnant women. Methods Randomized, crossover open labeled study in 135 pregnant women attending outpatient clinics in Ontario and Quebec. Results Use of PregVit® was associated with a 30% reduction in constipation rate as compared to Materna®. Both products demonstrated similar compliance rates. Compliance of Materna® was negatively associated with the severity of nausea and vomiting of pregnancy. No such correlation was found for PregVvit®. Conclusion PregVit®, a supplement with lower iron content (35 mg), has significantly decreased constipation rates as compared to 60 mg iron- Materna and has similar compliance rates. High iron content in multivitamin supplements is associated with adverse effects in pregnancy.